2014
DOI: 10.1039/c3ta14816e
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and highly nonstoichiometric titania (TiOx) thin films close to metal-like conductivity

Abstract: Oxygen-deficient titanium oxide films (TiO x) have been prepared by pulsed laser deposition at room temperature. Samples in their as-deposited state have an average composition of TiO 1.6 , are optically absorbing and show electronic conductivities in the range of 10 S cm À1. The films are metastable and consist of grains of cubic titanium monoxide (g-TiO) embedded in an amorphous TiO 1.77 matrix. Upon annealing in an argon atmosphere the electrical conductivity of the films increases and comes close to metal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 54 publications
(54 reference statements)
1
38
0
Order By: Relevance
“…For the sample with the band gap corresponding to TiO 2 (P7), the resistivity was in the order of 10 5 Ω cm. Similar results has been reported in the literature [20], where the samples with dark color exhibit low electrical resistivity; after a thermal annealing at 600°C the samples become transparent (due to the full oxidation of the TiO x film), increasing electrical resistivity in four orders of magnitude.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…For the sample with the band gap corresponding to TiO 2 (P7), the resistivity was in the order of 10 5 Ω cm. Similar results has been reported in the literature [20], where the samples with dark color exhibit low electrical resistivity; after a thermal annealing at 600°C the samples become transparent (due to the full oxidation of the TiO x film), increasing electrical resistivity in four orders of magnitude.…”
Section: Resultssupporting
confidence: 86%
“…Nakano et al [23] reported visible light photocatalytic activity of of oxygen deficient TiO 2 films obtained by Ar/H 2 plasma surface treatment; Dong et al [24] anodization for visible light photocatalysis; Lee et al [26] grew N-doped TiO x films using reactive sputtering reporting a red-shift band gap; and Leichweiss et al [20] grewn highly nonstoichiometric TiO x thin films, that shown high efficiency for water splitting reaction, using pulsed laser deposition at room temperature. Related to the activation of TiO 2 by infrared radiation, we only found the work of Gannoruwa et al [28], they reported that the nanocomposite Ag 2 O/TiO 2 was infrared active in the range from 800 nm to 1200 nm.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The compositions of the pellets were successfully verified using energy dispersive X‐ray spectroscopy measurements (Oxford INCA, Oxford Instruments). Using X‐ray diffraction measurements (θ/θ‐diffractometer, STOE & Cie GmbH with secondary monochromator or X'Pert Pro diffractometer, PANalytical, Almelo, Netherlands, with Ni‐Filter), the phase purity was investigated and the lattice parameters are in agreement to literature for Sm‐ and Gd‐doped ceria . Especially, the long‐lasting measurements with the X'Pert Pro diffractometer feature an outstanding resolution and signal‐to‐noise ratio ensuring the highly sensitive detection limit for impurities, which is required in this work.…”
Section: Methodsmentioning
confidence: 62%
“…In either case, the existence of off‐stoichiometry metal oxide surface may be used for redox‐based chemical catalysis. It is also interesting to note that thin epitaxial layers of cubic TiO have been characterized as superconductors with T C up to 7.4 K . Thus, the coverage of the BaTiO 3 crystals with a functional TiO x surface and the ability to pattern this phase locally may help nanoscale fabrication of superconducting‐based technologies.…”
Section: Resultsmentioning
confidence: 99%